Temperament, character, and quality of life in patients with schizophrenia and their first-degree relatives - Aukst-Margetić, Branka (Array, 2011)
The aim of this study was to investigate the associations between the temperament, character dimensions, and quality of life (QOL) of patients with schizophrenia ; their first-degree, nonaffected relatives ; and healthy control subjects. One hundred twenty patients, the same number of first-degree relatives, and the same number of control subjects were assessed using the Temperament and Character Inventory and the Quality of Life Enjoyment and Satisfaction Questionnaire. Patients were also assessed using the Positive and Negative Syndrome Scale. Patients and relatives had a significantly lower QOL than control subjects, controlled for temperament and character dimensions. Patients scored significantly higher than control subjects in harm avoidance and self-transcendence and lower in novelty seeking and selfdirectedness. First-degree relatives had lower results for novelty seeking and scored higher on self-transcendence than control subjects. Harm avoidance, self-directedness, and self-transcendence were the dimensions of Temperament and Character Inventory shown to be the most significant predictors of QOL. Psychopathology and age were also significant predictors of QOL. Our understanding of an individual patient's QOL must include personality evaluation